In-depth Analysis of IS6110 Genomic Variability in the Mycobacterium tuberculosis Complex - Jessica Comín; Jessica Comín; Isabel Otal; Isabel Otal; Isabel Otal; Sofía Samper; Sofía Samper; Sofía Samper (Frontiers in Microbiology)
The insertion sequence (IS) 6110 is a repetitive mobile element specific for the Mycobacterium tuberculosis complex (MTBC) used for years to diagnose and genotype this pathogen. It contains the overlapping reading frames orfA and orfB that encode a transposase. Its genetic variability is difficult to study because multiple copies are present in the genome. IS6110 is randomly located, nevertheless some preferential locations have been reported, which could be related to the behaviour of the strains. The aim of this work was to determine the intra- and inter-strain genetic conservation of this element in the MTBC. For this purpose, we analysed 158 sequences of IS6110 copies from 55 strains. Eighty-four copies were from 17 strains for which we knew all the locations in their genome. In addition, we studied 74 IS6110 copies in 38 different MTBC strains in which the location was characteristic of different families including Haarlem, LAM, S, and L6 strains. We observed mutation in 13.3% of the copies studied and we found 10 IS6110 variants in 21 copies belonging to 16 strains. The high copy number strains showed 6.2% of their IS6110 copies mutated, in contrast with the 31.1% in the low-copy-number strains. The apparently more ancient copy localised in the DR region was that with more variant copies, probably because this was the most studied location. Notably, all Haarlem and X family strains studied have an IS6110 in Rv0403c, suggesting a common origin for both families. Nevertheless, we detected a variant specific for the X family that would have occurred in this location after the phylogenetic separation. This variant does not prevent transposition although it may occur at a lower frequency, as X strains remain with low copy number (LCN) of IS6110.